Effectiveness of Differentiates E-LKPD on Excretory System to Increase Student’s Curiosity and Creative Thinking - Farhani, Lailatul; Syafii, Wan; Darmadi, Darmadi (FKIP - Universitas Riau, 2025)
This study aims to determine the effectiveness of E-LKPD Differentiation on the Excretory System material in increasing students' curiosity and creative thinking. The method used is a quasi-experimental design with a two-group pretest-posttest. The research sample was class XI.1 as the experimental class and XI.3 as the control class at SMAN 8 Pekanbaru. The instruments included questionnaires, curiosity observation sheets, and written creative thinking tests. Data analysis was carried out descriptively quantitatively. The results showed an increase in pretest and posttest scores. The independent sample t-test on curiosity showed a t-count value = 5.261 and t-table = 1.664, so H0 was rejected and H1 was accepted. This means that there is a significant difference between the curiosity of students in the experimental and control classes. The same test for creative thinking showed a t-count = 1.923 and t-table = 1.664, so H0 was rejected again. This shows a significant difference between the creative thinking abilities of students in the experimental and control classes. Thus, Differentiated E-LKPD is effective in increasing students' curiosity and creative thinking skills.